To solve the given system of equations:
- \( x - 3y = 18 \) (Equation 1)
- \( 7x - 5y = 46 \) (Equation 2)
Let's solve these equations step by step.
Step 1: Solve for \( x \) in terms of \( y \) using Equation 1.
From Equation 1: \[ x = 3y + 18 \]
Step 2: Substitute \( x \) into Equation 2.
Substituting \( x \) in Equation 2 gives: \[ 7(3y + 18) - 5y = 46 \]
Step 3: Expand and simplify.
\[ 21y + 126 - 5y = 46 \] Combine like terms: \[ 16y + 126 = 46 \]
Step 4: Solve for \( y \).
Subtract 126 from both sides: \[ 16y = 46 - 126 \] \[ 16y = -80 \] \[ y = -5 \]
Step 5: Substitute \( y \) back into Equation 1 to find \( x \).
Now substitute \( y = -5 \) back into the equation for \( x \): \[ x = 3(-5) + 18 \] \[ x = -15 + 18 \] \[ x = 3 \]
Final Solution
So, the solution of the system of equations is: \[ (x, y) = (3, -5) \]
Answer
The correct response is: (3, -5)